Solar-Powered Adsorption Cooling Using Activated Carbon and Methanol: Efficiency, Feasibility, and Optimization Pathways - Listiawati, Listiawati; Istanti, Joevanca; Ivandy, Mario (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2024)
This research investigates the viability and performance of a solar-powered adsorption cooling system employing activated carbon and methanol as the adsorbent-adsorbate pair. The study aims to assess the system's effectiveness in harnessing solar energy for cooling purposes while evaluating its efficiency, environmental impact, and economic feasibility. The research methodology involves comprehensive material characterization, prototype design, experimental testing, computational simulations, and performance evaluations. Material characterization confirms activated carbon's high surface area and porosity, validating its suitability for methanol adsorption. Experimental tests demonstrate the system's notable cooling capacity, coupled with moderate coefficient of performance (COP), emphasizing its feasibility. Insights into adsorption-desorption kinetics, temperature dependencies, and energy efficiency metrics reveal optimization pathways for enhancing system performance. Environmental assessments underscore the system's reduced carbon footprint and economic evaluations suggest promising long-term viability despite initial installation costs.